Pediatric Rheumatology A Clinical Viewpoint - Sawhney, Sujata; Aggarwal, Amita; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book on rheumatology in children is intended to be a handy tool for all professionals interested in this field. It is divided into five sections: General considerations, arthritic problems, connective tissue diseases, systemic vasculitides and finally a section that covers miscellaneous issues such as Immunodeficiencies, bone heath and uveitis. The book has an easy format with each chapter having one or more clinicalvignettes at the start of the chapter. In addition each chapter outlines the learning objectives and key take home messages. At the end of each section a collection of cases to highlight important issues in the clinic are included. The colorful charts, pictures and tables make reading this book an easy task. The authors are leading experts in their fields working at best practices centers globally to provide the reader with state-of-the-art information.
Part I: Introduction to Pediatric Rheumatology -- History of Pediatric Rheumatology -- Basic Immunology for the Pediatrician -- Genetics of Pediatric Rheumatic Diseases -- Human Joint Anatomy and Physiology -- Epidemiology of Pediatric Rheumatic Diseases -- Trial Dezign and Collaborative Work in Pediatric Rheumatology -- Non Biologic Drugs in Rheumatology -- Biologic Response Modifiers in Pediatric Rheumatology -- Clinical Examination of the Child with a Rheumatic Disease -- Laboratory and the Pediatric Rheumatologist -- Imaging in Pediatric Rheumatology -- Transition: Moving from Pediatric to Adult Rheumatology Care -- Outcome measures in Pediatric Rheumatology -- Part II: Arthritis in Childhood -- Approach to a Child with Joint Pains -- Approach to a Child with a Limp -- Common Orthopedic Problems in Children -- Overview of Juvenile Idiopathic Arthritis -- Systemic Onset Juvenile Idiopathic Arthritis -- Juvenile Spondyloarthropathies -- Management of Juvenile Idiopathic Arthritis -- Infections and Arthritis in Childhood -- Macrophage Activation Syndrome -- Clinical Case Vignettes: Arthritis in Children -- Part III: Connective Tissue Diseases in Childhood -- Connective Tissue Diseases in Childhood: An Approach to the Diagnosis and Classification -- Pediatric and Neonatal Lupus -- Pediatric Lupus Nephritis -- Juvenile Dermatomyositis -- Antiphospholipid Antibody Syndrome in Childhood -- Juvenile Localized Scleroderma -- Juvenile Systemic Sclerosis -- Undifferentiated Connective Tissue Disease, Mixed Connective Tissue Disease and Overlap Syndromes in Children -- Clinical Case Vignettes : Connective Tissue Diseases in Children -- Part IV: Vasculitis in Childhood -- Pediatric Vasculitis: Classification and Clinical Approach -- Henoch Schnolein Purpura -- Kawasaki Disease -- Granulomatosis with Polyangiitis in Children.-Childhood Polyarteritis Nodosa -- Behcets Disease -- Pediatric Takayasu arteritis -- Childhood Central Nervous System Vasculitis -- Cogans Syndrome and other Vasculitides in Children -- Clinical Case Vignettes: Childhood Vasculitis -- Part V: Miscellaneous Rheumatic Diseases in Childhood -- Autoinflammatory syndromes in children -- Metabolic bone disease and osteoporosis in children -- Joint Hypermobility and Pain Syndromes in Children -- Childhood Sarcoidosis -- Rheumatic Manifestations of Genetic Disorders and Hemophilia -- Immunodeficiency and Rheumatic Diseases -- Pediatric Uveitis.
Keywords: Medicine; Rheumatology; Pediatrics; Medicine & Public Health; Rheumatology; Pediatrics